Gambaran Pengetahuan Ibu Hami Hamil Tentang Teknik Woolwich Massage Terhadap Peningkatan Produksi ASI Di Puskesmas Sangurara - Sofyana, Sherllia; Musdalifah, Musdalifah; Sakulat, Gabriella (Bunda Edu-Midwifery Journal (BEMJ), 2024)
Low exclusive breastfeeding is a threat to child growth and development which will affect the growth and development of the quality of human resources. woolwich massage is performed on the breast and back muscles of postpartum women so as to trigger the oxytocin hormone to express breast milk considering the importance of exclusive breastfeeding from birth-age 6 months in order to increase optimal growth, development and health in infants. The coverage of exclusive breastfeeding in Indonesia is 65.16% with a target achievement of 90%.The purpose of this study was to provide education about woolwich massage to pregnant women to increase knowledge about woolwich massage conducted at Sangurara Health Center, with 32 pregnant women as respondents. Education was carried out by counseling method about efforts to increase breast milk production with a combination of woolwich. Before counseling, the average value of maternal knowledge about woolwic was in the insufficient category and after the provision of education the mother's knowledge level increased to the sufficient category with a P-Value of 0.04 so it can be concluded that there is an effect of providing education on increasing the knowledge of pregnant women about woolwich massage.